“I’m Not Sure if They’re Really Getting What I’m Saying”: Perspectives of Healthcare Professionals on the Need to Strengthen Sensory-Loss-Specific Healthcare for Older Adults During and Post COVID-19 in Canada - Atul Jaiswal; Shreya Budhiraja; Abinethaa Paramasivam; Sangeetha Santhakumaran; Shikha Gupta; Norman Robert Boie; Marie Savundranayagam; Claude Vincent; Edeltraut Kröger; Walter Wittich (Journal of Ageing and Longevity, 2026)
Background: The COVID-19 pandemic and related public-health measures, including physical distancing and the use of personal protective equipment (PPE), disrupted routine healthcare communication and care delivery for older adults with combined hearing and vision loss, or dual sensory loss (DSL). Around 1.1 million older Canadians are living with DSL and rely on multimodal communication to support assessment and continuity of care. Objectives: This study explored healthcare professionals’ (HCPs) perspectives on older adults with DSL accessing health services and information, and providers’ challenges delivering care during and after COVID-19. Methods: Following a nationwide online survey with 228 HCPs in Canada, in-depth qualitative interviews were conducted with 24 survey respondents to obtain their insights. Data were analyzed using qualitative content analysis. Results: HCPs reported that the pandemic introduced novel challenges due to the lack of training and technical resources to facilitate healthcare communication with their patients with DSL. HCPs faced difficulty in clinical assessments and diagnosis due to restrictions while using PPE, such as masks. Participants reported strategies such as alternative formats, use of gestures or pictures, assistive devices, and caregiver support and accompaniment that helped provide services to older adults with DSL. Conclusions: Study findings suggest that older adults with DSL were underserved during the pandemic and underscore the need for continuing education/training on DSL for HCPs in order to provide better care to this group.